Determination of Ex Officio Leadership, Organizational Culture, Loyalty, and Organizational Commitment towards Job Satisfaction through Career Path in Batam Employee Agency Employees - Syukur, Ihram Bani; Wibisono, Chablullah; Indrayani, Indrayani; Satriawan, Bambang; Dewi, Nolla Puspita (Universitas Pendidikan Ganesha, 2024)
The establishment of the ex-officio position in Batam, as mandated by Government Regulation Number 62 of 2019, created a unique governance structure in the Batam Business Board, held by the Mayor of Batam. This research investigates the impact of this governance model on economic growth and its potential influence on employee job satisfaction within the framework of the Batam Free Trade Zone and Free Port. Utilizing a mixed-method approach, the study encompasses both quantitative analysis using Structural Equation Modeling (SEM) via PLS software and qualitative insights through Resource Interviews. A total population of 444 was considered, with a sample of 221 respondents derived using the Slovin formula. Findings from the research demonstrate a substantial joint or simultaneous influence of the variables Ex Officio Leadership, Organizational Culture, Loyalty, and Organizational Commitment on Job Satisfaction. The study highlights the significant role of Ex Officio Leadership in shaping economic outcomes and employee satisfaction in Batam, proposing that such governance models could help reconcile the operational dualities between government and business entities in the region.